The determinants of chinese aid to Latin America and the Caribbean (2019)
The US-led global order, in the last two decades, has been characterized by China's emergence, sparking an intense debate about its potential impact over the different aspects of the international system. While in the international trade, financial and monetary system China is being gradually socialized within the status quo, in the development system the Asian giant has resisted any attempt of cooptation by the OECD-DAC to the point that it has created a parallel system to deliver its foreign aid according to its own values and following its own interests, which has led several authors to talk about a "silent revolution" in the international cooperation system. While extensive research has been conducted on the impact of Chinese aid to Africa, this paper will focus instead on Chinese aid to Latin America and the Caribbean. Through the use of multilevel regressions, this PhD thesis will empirically test several claims about the underlying Chinese aid, such as its preference for authoritarian and corrupt countries, the use of aid to achieve access natural resources and hydrocarbons or to favor the implementation of the One-China policy, among others. The results of the analysis suggest that most of the most worrying claims are unsubstantiated and that China's aid flows to LAC respond to motivations that resemble those of traditional donors (such as the US, Germany and Spain). Consequently, the region has everything to gain from the US-China competition for influence, with the condition of being able to avoid a replication of the center-periphery model and instead adopting an assertive stance to determine its own priorities and policies.